2018
DOI: 10.3390/min8030095
|View full text |Cite
|
Sign up to set email alerts
|

Fossilization History of Fossil Resin from Jambi Province (Sumatra, Indonesia) Based on Physico-Chemical Studies

Abstract: A unique specimen of fossil resin originating from the Dipterocarpaceae tree family found in Miocene brown coal deposits in Jambi Province (Sumatra, Indonesia) was investigated via microscopic observations, microhardness testing and infrared and Raman spectroscopic methods. Its form is rare in nature, being an aggregate of three varieties of resin differing in colour, transparency and internal structure. This suggests the formation of the resins at different stages. Further alteration processes, including foss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Some of the authors [44] determine the degree of resin maturity based on the ratio of 1650/1440 cm -1 bands in Raman spectroscopy. Recent investigations [26,34] did not confirm such relation. Correlation of spectral properties of resins with their age and maturity still requires more investigations.…”
Section: Structural Changes-ft-irmentioning
confidence: 80%
See 1 more Smart Citation
“…Some of the authors [44] determine the degree of resin maturity based on the ratio of 1650/1440 cm -1 bands in Raman spectroscopy. Recent investigations [26,34] did not confirm such relation. Correlation of spectral properties of resins with their age and maturity still requires more investigations.…”
Section: Structural Changes-ft-irmentioning
confidence: 80%
“…As it was previously reported [3], the resin fossilization runs through polymerization of nonvolatile ingredients, cross-linking and isomerization, after low molecular mass compounds have been evaporated. This means that thermal behavior may reflect maturation histories and resin transformations [26].…”
Section: Resultsmentioning
confidence: 99%
“…The aim of the study was also to find the most selective analytical tool for tracking the difference in chemical composition of fossil resins from a similar botanical origin that formed and altered in different geological conditions. Furthermore, this contribution is a kind of resumption of our previous studies on Sumatran resins 16 , providing additional data on their similarities and differences to glessite, which coexist within the same classification based on GC–MS class and NMR group.…”
Section: Introductionmentioning
confidence: 91%
“…In earlier investigations, it was found that the maturation of fossil resins has been influenced by various geological factors (e.g. volcanism, hydrothermal heating), not aging itself 8 , 10 , 11 , 14 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation